Plan de negocios para la creación de una microempresa dedicada a la comercialización de productos cárnicos en la ciudad de El Empalme, año 2013. - Tovar Carrera, Angel Josué (2015)
This research takes a business plan for the creation of a small business dedicated to the marketing of meat products in Junction City in 2013, to give people a better alternative Canton when buying meat products. To determine the location of the project was the qualitative method for point, sectors of Quevedo, showing that the optimal place for the project is in San Camilo, we examined the surveying market environment for producers of purified water and consumer, in which producers prefer to produce and sell purified water in 20-liter bottles, because of its high preference on the final consumer. The information provided was crucial consumer deciding on preferences that this is the product you buy. The financial study released economic viability of the project, with indicators such as the $170.846,83 USD NPV and IRR of 120,23%, obtaining information about the project's viability. It was concluded that the project is an alternative production and execution is recommended, based on the proposal suggested in order to ensure profitability.